STATUS GIZI BALITA DITENTUKAN OLEH PENGETAHUAN IBU TENTANG MAKANAN PENDAMPING ASI (MP-ASI) - Yuni Astuti Anggraini, Tyasning (MEDIA ILMU KESEHATAN, 2012)
Background: Improving the nutritional status of the community is one of the basic formation of qualified human resources. Under-five is the most decisive period in human development because it is the most critical period mainly viewed from the aspects of nutrition and health. To achieve optimal growth and development, WHO/UNICEF recommend four important things to do, one of which is providing comple- mentary foods in addition to breast milk (MP-ASI) since infants are aged 6 to 24 months or more. Maternal knowledge about complementary feeding is very important especially if associated with nutritional status as knowledge is included indirect factors that influence nutritional status. Objective: To determine the relationship between the level of maternal knowledge about comple- mentary feeding and the under-five nutritional status in Ngestiharjo Village. Methods: This was an observational, descriptive, analytic study with a cross sectional design. The population was all pairs of mother-under-five, amounting to 190 samples that had been adapted to the criteria of the children aged 6-24 months. Sample was determined with Quota Sampling. Data collection used observation sheets and questionnaires. Analysis used the Kendall Tau test. Results: The level of maternal knowledge about MP-ASI was that the majority was in good category by 87.4%. On the under-five nutritional status, mostly the under-five children had good nutritional status by 84.2%. The result of the hypothesis with Kendall Tau correlation obtained p value = 0.005. Conclusion: There was a significant relationship between the level of maternal knowledge about complementary feeding and the under-five nutritional status. Good knowledge about complementary feeding will reduce the risk of lack of nutrition or malnutrition in under-five children. Keywords: Complementary foods in addition to breast milk, nutritional status, under-five